Should competition laws in ASEAN promote non-efficiency goals? - Abdul Rahman, Nasarudin; Ahamat, Haniff (2016)
Competition law seeks to preserve the process of competition in the market with the belief that competition produces an optimal outcome in the market: encouraging firms to be efficient and making consumers better off. Therefore, the realization of economic efficiency is at the heart of the competition law enforcement. However, for many developing economies, the objective of the competition law is more than the realization of economic efficiency. Competition authorities are always confronted with various other conflicting goals which may not related to economic efficiency in its true sense to promote the so called ‘socio-economic development’. This paper attempts to answer several questions: should the competition law promote non-efficiency goals? What kind of non-efficiency goals should it promote? How non-efficiency goals should be promoted through the lens of competition law? Who decides which goals? This paper found that ASEAN member states have put in place diverse objectives for their competition laws to tailor the implementation of the competition laws to the local conditions. It is argued that pursuing multiple objectives may create tensions between promoting economic efficiency on the one hand and promoting non-economic goals on the other hand. It further complicates the process of harmonization of the competition laws in ASEAN and poses as a main obstacle to ASEAN economic and market integration. It is suggested that competition laws should focus on promoting economic efficiency. Other non-economic goals such as social goals should be best pursued through other policies. Should the competition laws be used to promote non-economic goals, it should be limited in scope, pursued in a transparent manner and should be accompanied with the principle of proportionalities.